Autonomous Flying Robots Unmanned Aerial Vehicles and Micro Aerial Vehicles - Nonami, Kenzo; Kendoul, Farid; Suzuki, Satoshi; Wang, Wei.; Nakazawa, Daisuke; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2010)
Worldwide demand for robotic aircraft such as unmanned aerial vehicles (UAVs) and micro aerial vehicles (MAVs) is surging. Not only military but especially civil applications are being developed at a rapid pace. Unmanned vehicles offer major advantages when used for aerial surveillance, reconnaissance, and inspection in complex and inhospitable environments. UAVs are better suited for dirty or dangerous missions than manned aircraft and are more cost-effective. UAVs can operate in contaminated environments, for example, and at altitudes both lower and higher than those typically traversed by manned aircraft. Many technological, economic, and political factors have encouraged the development and operation of UAVs. New sensors, microprocessors, and propulsion systems are smaller, lighter, and more capable, leading to levels of endurance, efficiency, and autonomy that exceed human capacities. Comprising the latest research, this book describes step by step the development of small or miniature unmanned aerial vehicles and discusses in detail the integrated prototypes developed at the robotics laboratory of Chiba University. With demonstration videos, the book will interest not only graduate students, scientists, and engineers but also newcomers to the field.
Modeling and Control of Small and Mini Rotorcraft UAVs -- Fundamental Modeling and Control of Small and Miniature Unmanned Helicopters -- Autonomous Control of a Mini Quadrotor Vehicle Using LQG Controllers -- Development of Autonomous Quad-Tilt-Wing (QTW) Unmanned Aerial Vehicle: Design, Modeling, and Control -- Linearization and Identification of Helicopter Model for Hierarchical Control Design -- Advanced Flight Control Systems for Rotorcraft UAVs and MAVs -- Analysis of the Autorotation Maneuver in Small-Scale Helicopters and Application for Emergency Landing -- Autonomous Acrobatic Flight Based on Feedforward Sequence Control for Small Unmanned Helicopter -- Mathematical Modeling and Nonlinear Control of VTOL Aerial Vehicles -- Formation Flight Control of Multiple Small Autonomous Helicopters Using Predictive Control -- Guidance and Navigation of Short-Range UAVs -- Guidance and Navigation Systems for Small Aerial Robots -- Design and Implementation of Low-Cost Attitude Quaternion Sensor -- Vision-Based Navigation and Visual Servoing of Mini Flying Machines -- Autonomous Indoor Flight and Precise Automated-Landing Using Infrared and Ultrasonic Sensors.
Keywords: Engineering; Computer hardware; Engineering; Control, Robotics, Mechatronics; Computer Hardware